Sonerila dongii (tribe Sonerileae, Melastomataceae), a new species from Lam Dong province, South Vietnam - Nguyen, Danh Duc; Nguyen, van Canh; Lin, Che Wei (Phytotaxa, 2024)
Sonerila dongii, a new species from Lam Dong province in South Vietnam, is described and illustrated here. The morphological characteristics of this new species distinguish it from any previously documented species in the Indochina region because it lacks a tuber and likely adapts to periodic drought seasons by utilizing its fleshy stems. Sonerila dongii bears a resemblance to S. peninsularis with its variegated, ovate foliage, and stem and inflorescence covered with minutely brown glandular trichomes. However, the new species differs from S. peninsularis in lacking an underground tuber (vs. tuber present), stem terete (vs. quadrangular) and branched (vs. usually unbranched), petals glabrous (vs. abaxial surface with long stipitate glandular trichomes) and longer anthers 4.5–5 mm long (vs. 1.5–2.5 mm). The conservation status of Sonerila dongii is assessed as data deficient (DD), according to the IUCN Red List Categories and Criteria.